2018
DOI: 10.1038/s41598-018-21675-5
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of positive and confusing hand X-ray signs in diagnosing Kashin–Beck Disease in children in China

Abstract: When screening for Kashin–Beck disease (KBD) in children, hand X-ray examination is the most important measure. However, there is high rate of misdiagnosis because of confusing X-ray signs. We studied the characteristics of positive and confusing hand X-ray signs. Clinical and radiological examinations were conducted in all 7- to 12-year-olds in selected villages from some KBD and non-KBD areas. We analysed the radiological and epidemiological characteristics of the X-ray signs of KBD and the confusing signs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…14 Data science methods and traditional machine learning methods can also be used to make diagnoses 15,16 and deep learning techniques have been used to aid the diagnosis of KBD. 17 However, due to the challenging features of positive hand X-ray signs in diseased children, 18,19 there is significant scope for improving the extraction and utilization of image information.…”
Section: Introductionmentioning
confidence: 99%
“…14 Data science methods and traditional machine learning methods can also be used to make diagnoses 15,16 and deep learning techniques have been used to aid the diagnosis of KBD. 17 However, due to the challenging features of positive hand X-ray signs in diseased children, 18,19 there is significant scope for improving the extraction and utilization of image information.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound is also widely used in the diagnosis of musculoskeletal diseases in children and adolescents because of its advantages of being fast and radiation-free. However, for older children with osteochondral structure becoming more mature, ultrasound is limited in the range of display by bone shadow, resulting in the overlapping phenomenon and affecting the diagnosis results [7,8]. CT examination has a good display effect on fracture fragments and has a good guiding role in preoperative evaluation and planning.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the diagnosis of KBD mainly depends on the X-ray examination [13][14][15][16] which could not reflect early damage of growth plate and cartilage sensitively [17]. A latest systematic review found that the X-ray detective rate of KBD was 11% depending on the study [18].…”
Section: Introductionmentioning
confidence: 99%